Sitting less at work: a qualitative study of barriers and enablers in organisations of different size and sector - Kelly Mackenzie; Elizabeth Such; Paul Norman; Elizabeth Goyder (BMC, 2019)
Abstract Background Prolonged sitting is associated with a range of chronic health conditions and working in office-based jobs is an important contributor to total daily sitting time. Consequently, interventions to reduce workplace sitting have been developed and tested; however, no single intervention strategy consistently produces reductions in workplace sitting time. Exploring barriers and enablers to sitting less at work has been shown to support the development of more effective interventions. In order to address these barriers and enablers during the development and implementation of sit less at work interventions, it is important to understand how they may differ in different types of organisation, an area which has not yet been explored. The main aim of this study was to determine whether barriers and enablers to sitting less at work varied between organisations of different size and sector. Methods A qualitative study design was used. Four organisations of different sizes and sectors participated: a small business, a charity, a local authority and a large corporation. A total of ten focus groups comprising 40 volunteer employees were conducted. Focus groups were audio-recorded and transcribed verbatim. Transcripts were then thematically analysed using pre-defined themes, but analysis also allowed for emergence of additional themes. Results Barriers and enablers which were consistently raised by participants across all four organisations primarily included: individual-level factors such as habits and routines, and personal motivations and preferences; and factors relating to the internal physical environment. Barriers and enablers that differed by organisation mainly related to: organisational-level factors such as organisational culture, organisation size, and ways of working; and factors relating to the broader social, economic and political context such as the idea of presenteeism, and the impact of wider economic and political issues. Conclusions This study found that although some themes were consistently raised by participants from organisations of different size and sector, participants from these organisations also experienced some different barriers and enablers to sitting less at work. For future research or practice, the study findings highlight that organisation-specific barriers and enablers need to be identified and addressed during the development and implementation of sit less at work interventions.